Glomerulopatias no hospital universitário Cassiano Antônio de Moraes : revisão do banco de dados de biópsias renais - Naseri, Alice Pignaton (2016)
Introduction: Glomerulopathy (Gp) corresponds to the third leading cause of progression to chronic kidney disease in the world. There is a wide variety of histological types, and each has its own characteristics and specific treatment according to its pathogenesis. They can be primary or secondary. Objective: Identify the most prevalent types of Gp in a referral hospital in Espirito Santo (ES), the main clinical indications for performing the Renal Biopsy (RxB) and the adequacy of the sample of renal cortex; Knowing the epidemiological data (age, gender, color of the skin) and laboratory (proteinuria / 24 hours, serum creatinine, glomerular filtration rate and serum albumin) general of Gp in a referral hospital. Method: Cross-sectional retrospective study reports histopathologic review of Gp filed in the electronic registration of the Pathological Anatomy Department of HUCAM in the Federal University of Espírito Santo (UFES) and analysis of their medical records filed in the Statistical and Medical Archive Service (SMAS) of HUCAM / UFES from January 2008 to December 2015. Results: 415 histopathology reports were reviewed. The primary Gp corresponding to 215 cases (51.8%). Secondary Gp accounted for 190 cases (45.78%). Chronic Gp (not otherwise specified) accounted 10 cases (2.4%). Of the total revised reports, 415, FSGS was the most frequent primary Gp (108/26%), followed by MGp (40 / 9.6%), MPGp (34 / 8.19%), MCD (14/3, 37%), IgAN (13 / 3.13%), DAGp (3/ 0.72%), Crescentic Gp (2 / 0.48%) and mesangial proliferative glomerulonephritis not IgA (1/0,24%). Of the total revised reports, 415, lupus nephritis (LN) is the most common secondary Gp with 174 cases (41.9%), followed by lupus like nephritis (10 cases / 2.4%), diabetic nephropathy (4 / 0.96 %) and amyloidosis (2 / 0,48%).The Renal Biopsy (RxB) indications for suspected Gp were mainly nephrotic syndrome – NOS- (52.5%) and LN (21.6%). The median number of glomeruli in kidney cortex was 10 glomeruli. The Gp, generally predominated in females (62.27%), in brown (46%) and 3rd (25.9%) and 4th (22.27%) decades of life. The median of 24h proteinuria was 3500mg / 24h, the creatinine was 1.1 mg / dL and GFR was 80ml / min / m², with serum albumin 2,34mg / dL. Conclusion: LN was the most frequent primary Gp followed by FSGS. The main clinical indication for RBx was NOS. The samples of renal cortex were adequate for histopathological evaluation. The Gp predominated in brown individuals, females, between 3rd and 4th decades of life, with nephrotic proteinuria and mild lowering renal function.